Thrips infestation and pod yield of cultivar "IAC Sempre Verde" under different pest management approaches and plant density - Ruiz, Fábio Fiori (2021)
To serve the segment of organic peanut production, a cultivar IAC Semper Verde was developed, highly resistant to leaf spots, but which still requires studies with regard to the control of invasive plants and pest insects. Therefore, the objective of this work was to evaluate thrips infestation, damage, and the effects on pod yield of this cultivar submitted to two phytosanitary managements and three sowing densities. The experiment was carried out at the Advanced Sugarcane Research Center, in Ribeirão Preto-SP, in the 2020/21 season, using a randomized block design in a factorial scheme (2 x 3) with four replications, with two types of phytosanitary management (conventional and organic) and three sowing densities (12, 16 and 20 seeds per meter). The density of 16 seeds per meter, in line with the conventional management, provided the lowest rate of infestation and damage by thrips, generating higher productivitys.